Comparative Analysis of Eximius Med and MNPS Software for Stereotactic Neurosurgical Planning: A Precision and Accuracy Study - Anjos, Klécia Santos dos; Costa, Maria Clara Cruz Moraes; Vieira, Maria Elisa Sobral Vila Nova de Carvalho; Oliveira Santos, Bruno Fernandes de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
To compare the geometric registration in the Eximius Med (Artis Tecnologia) and MNPS (Mevis Informática Médica LTDA.) stereotactic software.The study design included acquisition of skull images by computed tomography, marking of point coordinates (X, Y, and Z) in the MNPS and Eximius Med software performed by two independent evaluators, and statistical evaluations of precision and accuracy. Data were expressed as means, variances, and standard deviation. For comparisons between variables, the Euclidean distance, Student's t-test, Levene's test, the calculation of Cohen's D, and the intraclass correlation coefficient (ICC) were used. Values of p < 0.05 were considered statistically significant.The mean Euclidean distance was 0.07 ± 0.056 (95%CI: −0.037–0.18) mm. It is possible to state that there is a submillimetric difference in the coordinates with low effect size between the measurements made in Eximius and MNPS. The intraobserver evaluation showed that there is a positive correlation (ICC = 1) in the markings of each evaluator, while in the interobserver evaluation, there was no significant difference in any of the coordinates (p > 0.5) between the two software, when comparing evaluators 1 and 2.Eximius Med, therefore, is a consistent, comparable, precise, and highly accurate alternative for use in cranial stereotaxy.
Keywords: neurosurgery; software; imaging; three-dimensional